South Africa : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper for South Africa presents a quantitative analysis of inflation dynamics in the country. The conduct of monetary policy has been complicated by a variety of unanticipated events that have had important effects on inflation. Exposed to exchange rate and other shocks, the model confirms that a delayed policy response to inflation shocks leads to persistently higher inflation rates and, subsequently, to a sharp real contraction of the economy.